The 2026 western US snow drought was about four times more likely due to climate change - Adrienne M. Marshall; Marianne Cowherd; Stefan Rahimi; Yuhong Ye (Proceedings of the National Academy of Sciences, 2026)
In the spring of 2026, anomalously low snow conditions in the western United States threatened winter recreation and water supplies. Here, we investigate: to what extent was this snow drought attributable to the climate change that has occurred since the pre-industrial period? We find that a snow drought this severe across the western United States was approximately 4.4 [95% CI: 2.6, 9.4] times more likely in the current climate than in the preindustrial period. In the Upper Colorado River Basin, the snow drought was approximately 14 times more likely [0.09, 4,300]. Given a projected increase in the frequency of snow droughts at least this severe in a moderately high emissions warming scenario, the lived experience of this event may help scientists, resource managers, and the public consider what western US snow might look like if greenhouse gas emissions are not aggressively reduced.